Show why the value converges to π\pi

a0=1a_0=1

an+1=an+sin(an)a_{n+1}=a_n+\sin{(a_n)}

Explain why the following occurs:

a0=1a_0=1

a1=1+sin(1)1.841470985a_1=1+\sin{(1)}\approx 1.841470985

a2=1+sin(1)+sin(1+sin(1))2.805061709a_2=1+\sin{(1)}+\sin{(1+\sin{(1)})}\approx 2.805061709

a3=1+sin(1)+sin(1+sin(1))+sin(1+sin(1)+sin(1+sin(1)))3.135276333a_3=1+\sin{(1)}+\sin{(1+\sin{(1)})}+\sin{(1+\sin{(1)}+\sin{(1+\sin{(1)})})}\approx 3.135276333

a43.141592612a_4\approx 3.141592612

a53.141592654πa_5\approx 3.141592654\approx\pi

Note by Jack Han
4 years, 5 months ago

No vote yet
1 vote

</code>...<code></code> ... <code>.">   Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in </span>...<span></span> ... <span> or </span>...<span></span> ... <span> to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Sort by:

Top Newest

Let's see here...

The interesting thing I was talking about is the fact that the given series always converges into a value ana_n such that sin(an)=0sin(a_n)=0 for different values of a0a_0. To put it in more exact terms, it always converges to a value of ana_n such that cos(an)=1an=mπcos(a_n)=-1\Rightarrow a_n=m\pi, where mm is an odd integer. (mm can also be even, but that is a degenerate case where all terms are same)

I'm going to use something here that I actually learned from gradient descent. If you don't know what it is, you can google it. But, the mathematics used below is an extremely tame form and is easy to understand with little knowledge of calculus.

Consider the function f(x)=cos(x)df(x)dx=sin(x)f\left( x \right) =\cos { (x) } \\ \Rightarrow \frac { df\left( x \right) }{ dx } =-\sin { (x) }

Now see what happens when we take some arbitrary value of xx (say x=1x=1)and then do the following repeatedly:

x:=xdf(x)dx=x+sin(x)x:=x-\frac { df\left( x \right) }{ dx }=x+\sin { (x) } (":=" is the assignment operator )

In the above figure, we can see two points marked. One is red, which represents the first value of xx(=1=1). The other is brown, and is after one iteration of above step.

We can see that when we do x:=x+sin(x)x:=x+sin(x), what is actually happening is that xx is surfing along the slope of the curve cos(x)cos(x). We move the value of xx down the tangent. Change xx little by little, so that finally, after many iterations it moves closer and closer to the minima, i.e x=πx=\pi.

I know this is not a definitive proof of what happens... I'm sure you will realize the importance of this once you understand what is happening.

In general, series defined as an=an1αdf(an1)dan1a_n=a_{n-1}-\alpha\frac { df\left(a_{n-1} \right) }{ da_{n-1} }

Will converge to the nearest value of aa (nearest to a0a_0) such that f(a)f(a) is minimum, provided the value of α\alpha is not too large.

Raghav Vaidyanathan - 4 years, 5 months ago

Log in to reply

Yes, that was awesome, that is basically the newton Rhapsody method of estimation of roots, doing the following iteration for any curve will eventually lead us to the nearest root, that is great, actually i think this is pretty much the solution +1

Mvs Saketh - 4 years, 5 months ago

Log in to reply

Good work! Newton's method for estimating roots.

Pretty much seals the deal. Great solution +1.

Shashwat Shukla - 4 years, 5 months ago

Log in to reply

Good work.

Jack Han - 4 years, 5 months ago

Log in to reply

Log in to reply

As usual, since the series converges.. this means that when nn\to\infty ,

an+1=ana_{n+1}=a_{n}. But an+1=an+sin(an)a_{n+1}=a_{n}+sin(a_{n})

sin(an)=0\Rightarrow sin(a_{n})=0

Now how do we know that an=πa_{n}=\pi? We know this since a0=1a_0=1 and the series is constantly increasing. Therefore, it converges onto the first value of x>1x>1 such that sin(x)=0sin(x)=0.

Raghav Vaidyanathan - 4 years, 5 months ago

Log in to reply

Bro , But It is not always true limn(an)=limn(an+1)\lim _{ n\rightarrow \infty }{ ({ a }_{ n }) } =\lim _{ n\rightarrow \infty }{ { (a }_{ n+1 }) } .

Deepanshu Gupta - 4 years, 5 months ago

Log in to reply

Why not? Do you have a counter-example?

Shashwat Shukla - 4 years, 5 months ago

Log in to reply

Which value converges to pi ??

Vighnesh Raut - 4 years, 5 months ago

Log in to reply

If you call L the value of the limit you obtain sin(L)=0. Now L can be pi or zero but zero is impossible because of the initial condition. More precisely you can say that the value of the sequence is LOW bounded

Matteo De Zorzi - 4 years, 5 months ago

Log in to reply

This is turning out to be very interesting...

I want to know if we can find a general form for a function f(x)f(x) such that the series a1,a2,...a_1,a_2,... defined by:

an+1=an1+f(an1)a_{n+1}=a_{n-1}+f(a_{n-1})

Converges for a given value of a0a_0.

Further, is it true that all of the values of such ana_n as nn\to \infty satisfy f(an)=0f(a_n)=0?

Raghav Vaidyanathan - 4 years, 5 months ago

Log in to reply

I think the answer to this is going to be extremely interesting.... I have a feeling... Is anyone else thinking what I'm thinking?

Raghav Vaidyanathan - 4 years, 5 months ago

Log in to reply

What are you thinking?

Shashwat Shukla - 4 years, 5 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...